The Evolving Genomic Landscape of Esophageal Squamous Cell Carcinoma Under Chemoradiotherapy - Hirata, Hidenari; Niida, Atsushi; Kakiuchi, Nobuyuki; Uchi, Ryutaro; Sugimachi, Keishi; Masuda, Takaaki; Saito, Tomoko; Kageyama, Shun-Ichiro; Motomura, Yushi; Ito, Shuhei; Yoshitake, Tadamasa; Tsurumaru, Daisuke; et al. (Cancer research (Chicago, Ill.), 2021)
Esophageal squamous cell carcinoma (ESCC) often recurs after chemoradiotherapy, and the prognosis of ESCC after chemoradiotherapy has not improved over the past few decades. The mutation process in chemoradiotherapy-resistant clones and the functional relevance of genetic alterations remain unclear. To address these problems, we performed whole-exome sequencing of 52 tumor samples from 33 patients with ESCC who received radiotherapy combined with 5-fluorouracil/platinum. In multiregion analyses of pretreatment and locally recurrent lesions from five cases, most driver gene-altered clones remained under chemoradiotherapy selection pressure, while few driver gene alterations were acquired at recurrence. The mutation signatures of recurrent ESCC, including increased deletion frequency and platinum dose-dependent base substitution signatures, were substantially different from those of primary ESCC and reflected the iatrogenic impacts of chemoradiotherapy. Single-region analysis of 28 pretreatment tumors indicated that focal copy-number gain at the locus was significantly associated with poor progression-free survival and overall survival after chemoradiotherapy. gain remained throughout the chemoradiotherapy course and potentially contributes to intrinsic resistance to chemoradiotherapy. Consistent with these findings, copy number and mRNA and protein levels in ESCC cell lines correlated positively with resistance to radiotherapy, and knockdown improved sensitivity to radiotherapy. Overall, these data characterize the clonal evolution process induced by chemoradiotherapy and clinically relevant associations for genetic alterations in ESCC. These findings increase our understanding of therapeutic resistance and support the rationale for precision chemoradiotherapy. SIGNIFICANCE: Whole-exome sequencing reveals the genetic evolution of ESCC during chemoradiotherapy, highlighting gain in pretreatment tumors as a potential marker of therapy resistance.